Compliance in the First Four Years of AAS 27 Financial Reporting by Local Government: A Study of the New South Wales experience - Gregory K. Laing (Australasian Accounting, Business and Finance Journal, 2007)
This paper reports on a longitudinal study of the levels of compliance for the first four years (1994 to1997) following the introduction of the Australian Accounting Standard (AAS 27). The annual reports of all 177 local government councils in NSW were analysed revealing a high level of compliance with the standard. The main cause for non-compliance was the complexity of the recognition and treatment of assets. In addition a number of problems were identified, in particular the timeliness of the reports and the disproportionately high levels of depreciation expenses reported in the operating statement. The increased complexities of the financial management in Local Government imposed by AAS 27 required professional accounting competencies more appropriately derived from a degree level education which contributed to a high turnover of accounting staff during the four years. Finally, the paper questions the viability of the proposed dismantling of AAS 27 and the possible impact this might have upon the sector.
Keywords: AAS 27; Local Government Accounting; Australian Accounting Standard 27; Financial Reporting Compliance